Decent Work and Its Circumstances: Reflections on SDG 8 in the Context of Digital Capitalism. (Ágora de Heterodoxias, 2026)
This study assesses the viability of the "decent work" concept (SDG 8), concluding that a fundamental contradiction exists between its normative ideal and the metabolic trajectory of the capitalist system in the digital age. Employing a threefold methodology that combines bibliographic-documentary analysis, the theoretical frameworks of Ortega y Gasset, Bourdieu, and Mészáros, and Corpus-Assisted Discourse Analysis (using Antconc 4.3.1 software), this paper argues that the limited outcomes of the Decent Work Agenda are not simply implementation failures, but rather symptoms of capital's systemic logic, which structurally shifts risks onto the workforce. The analysis examines the contemporary labor paradox, wherein perceived autonomy in the platform economy masks profound precarity and self-exploitation. It further demonstrates that regulatory frameworks developed in the 20th century are structurally inadequate to address this new reality. Therefore, the study contends that the universalization of decent work is unviable under the current logic of capital, necessitating a fundamental redefinition of social justice principles for the digital era.
Keywords: Decent work; Digital capitalism; Sustainable Development Goal 8 (SDG 8)